2022
DOI: 10.1002/tcr.202200071
|View full text |Cite
|
Sign up to set email alerts
|

Porous Organic Polymers: Promising Testbed for Heterogeneous Reactive Oxygen Species Mediated Photocatalysis and Nonredox CO2 Fixation

Abstract: Catalysts play a pivotal role in achieving the global need for food and energy. In this context, porous organic polymers (POPs) with high surface area, robust architecture, tunable pore size, and chemical functionalities have emerged as promising testbeds for heterogeneous catalysis. Amorphous POPs having functionalized interconnected hierarchical porous structures activate a diverse range of substrates through covalent/non‐covalent interactions or act as a host matrix to encapsulate catalytically active metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 141 publications
0
6
0
Order By: Relevance
“…Flexible building blocks that do not fit together neatly, like aliphatic molecules or polymers with flexible side chains, can be used to create amorphous POPs. 105 POPs fall into three complementary groups: crystalline or amorphous, conjugated or non-conjugated, and semiconducting or heterogenized molecular analogues (Fig. 6A).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Flexible building blocks that do not fit together neatly, like aliphatic molecules or polymers with flexible side chains, can be used to create amorphous POPs. 105 POPs fall into three complementary groups: crystalline or amorphous, conjugated or non-conjugated, and semiconducting or heterogenized molecular analogues (Fig. 6A).…”
Section: Reviewmentioning
confidence: 99%
“…Flexible building blocks that do not fit together neatly, like aliphatic molecules or polymers with flexible side chains, can be used to create amorphous POPs. 105…”
Section: Classification Properties and Structures Of Porous Organic P...mentioning
confidence: 99%
“…For example, Abhijit and Arkaprabha reviewed the photocatalytic organic transformation of reactive oxygen species and nonredox fixation of CO 2 by amorphous POP. [43] Zhang et al summarized the application of metal-free and metal-containing carbazole CMPs in photocatalytic organic synthesis. [44] In this review, miscellaneous reported amorphous POPs are systematically classified, expecting to understand the current status of heterogeneous photocatalysts in the field of photocatalytic organic transformations (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, highly porous ionic metal organic frameworks (MOFs) explored for oxoanion removal often suffer from long-term stability in acidic or basic mediums. [18,19] In this context, porous organic polymers (POPs), owing to their tunable pore functionalities, high porosity, hierarchical pore size distribution, excellent hydrothermal and chemical stability, [20][21][22][23][24][25][26][27][28][29][30][31][32][33] have emerged as advanced adsorbent materials for molecular separation, including wastewater treatment. [31][32][33] Recently, ionic POPs, [33][34][35] fabricated through the integration of charged building blocks or post-synthetic modification, have been demonstrated as suitable materials for the removal of toxic oxoanions through an ion-exchange process.…”
Section: Introductionmentioning
confidence: 99%